Peran Serta Masyarakat dalam Menanggulangi Kasus Pencemaran dan/ atau Kerusakan Lingkungan Hidup - Dewi Fatmawaty; Hartuti Purnaweni; Yanuar Luqman (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Fatmawaty D, Purnaweni H, Luqman Y. 2020. The community participation in tackling cases of pollution and/or environmental damage. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The Law Number 32 of 2009 concerning Environmental Protection and Management in article 70 states the rights and opportunities for the community to play an active role in environmental protection and management. The roles that can be played by the community include: a) social supervision, b) providing suggestions, opinions, suggestions, objections, complaints; and/ or c) submission of information and/ or reports. However, the community participation is still not running optimally. It can be seen from the increasing number of pollution and or environmental damage cases from year to year. This review aims to find out how the implementation of community participation in handling cases of environmental pollution and / or damage as an effort to protect the environment and what obstacles are faced in this implementation. The scope of the article reviewed includes the role of the community and the role of the government in handling cases of pollution and or environmental damage. Cases of pollution and environmental damage are handled by the Government through supervision and law enforcement, and by involving community participation through social monitoring, filing complaints and submitting information and / or reports. The results of the review show that community participation is still not effective in overcoming cases of pollution or environmental damage.